Globalization and Contestation: The New Great Counter-Movement - Munck, Head of Civic Engagement Dublin City University and Visiting Professor of Development Studies University of Liverpool and St Mary's University Nova Scotia Ronaldo; Munck, Ronaldo (Routledge, 2006)
Globalization is undoubtedly the great overarching paradigm of our era. However, there is still little agreement on what globalization actually ‘is’ and some do not accept that it ‘is’ anything at all. This new book addresses the contestation of globalization by the anti- or counter-globalization movement. To contest means to challenge, to call into question, to doubt, to oppose and to litigate. This study shows how globalization is ‘contestable’ in many different ways and how the counter-movements we have seen emerging over the last decade also ‘bear witness’ on behalf of an alternative human future. Ronaldo Munck presents an overarching framework that allows us to understand how globalization and its contestation are inextricably bound up with one another. This volume insightfully explores a number of case studies, including: the battle of Seattle in 1999 the World Social Forum peasant internationalism environmental movements and reactionary movements including: the US Patriot's movement, Islamic fundamentalist movements and other nationalist movements. Globalization and Contestation will be of great interest to all students and scholars of international relations, politics and of globalization and global governance in particular.
Political Science; History
Keywords: countermovement; globalization; political economy; political science

Time–space intensification: Karl Polanyi, the double movement, and global informational capitalism - Ó Riain, Seán (Theory and Society, 2006)
This article advances the concept of “time–space intensification” as an alternative to existing notions of time–space distanciation, compression and embedding that attempt to capture the restructuring of time and space in contemporary advanced capitalism. This concept suggests time and space are intensified in the contemporary period – the social experience of time and space becomes more explicit and more crucial to socio-economic actors’ lives, time and space are mobilized more explicitly in individual and corporate action, and the institutionalization of time and space becomes more politicized. Drawing on Polanyi’s concepts of fictitious commodities and the double movement, and developing them through an analysis of work organization and economic development in the Irish software industry, the article argues that the concept of time–space intensification can add significantly to our understanding of key features of the restructuring of the temporal and spatial basis of economic development and work organization.
Sociology
Keywords: capitalism; double movement; fictitious commodities; social theory; time-space intensification

Understanding Global Capitalism: Passive Revolution and Double Movement in the Era of Globalization - Xing, Li; Hersh, Jacques (American Review of Political Economy, 2006)
This paper attempts to provide a framework for understanding the way globalization has reshaped the terrain and parameters of social, economic and political relations both at the national and global levels, and exerted pressure on the resiliency capacities of capitalism. It proposes to examine the ways social relations of domination and subordination are produced, reproduced and maintained while continuously undergoing transformations. Through conceptualizing the evolution of the capitalist world order in a historical perspective and by exploring the changes of relations brought about by the intensification of globalization since the 1990s, the objective is to generate a perspective for understanding such a process based on the application of Gramscian and Polanyian theoretical and analytical categories. The conclusion aims to convey that the process is contingent on both structures and agencies and it also produces the opposite result: i.e. reducing the legitimacy of capitalism's hegemony and especially limiting its resilient capacities.
Political Science
Keywords: capitalism; capitalist systems: political economy; colonialism; double movement; globalization; imperialism; international economic order; postcolonialism

Theorising globalisation's social impact: proposing the concept of vulnerability - Kirby, Peadar (Review of International Political Economy, 2006)
The concept of vulnerability was introduced into IR theorising by Keohane and Nye who saw it as one of the consequences of complex interdependence and it is being increasingly employed by IGOs to capture the impact of globalisation on society. However, the concept has been little used in the academic literature on globalisation, except in a descriptive sense. This article argues that the concept has the potential to fill a gap in the toolkit of the ‘new’ IPE, offering an analytical category that can capture the distinctive impact of globalisation on society more adequately than other concepts that are more widely used. The article begins by surveying how the concept has been used by Keohane and Nye and by IGOs. It then offers a definition and illustrates the application of the concept by describing some of the principal ways in which globalisation is increasing risk and eroding coping mechanisms. It goes on to argue that the concept of vulnerability captures in a fuller way the distinctive social impact of globalisation than do other concepts widely used in the IPE literature, examining in turn the limitations of the concepts of poverty/inequality, risk and insecurity. Finally, the article situates the concept of vulnerability within the social theory of Karl Polanyi, arguing that it expresses in the conditions of today's globalisation the threats to human livelihood from the inroads of the market that are widely referred to by scholars within the ‘new’ IPE, capturing better than do other concepts the key features of these threats as seen by Polanyi. The article concludes by proposing the concept of vulnerability as a core conceptual category for IPE scholars that offers the potential for the disciplinary field to generate more original insights into the social impacts of the political economy processes to the understanding of which it has made such a major contribution.
Political Science
Keywords: economics; globalisation; globalization; human security; industrial revolution; inequality; interdependence; international political economy; international relations; poverty; social impact; social problems; vulnerability

Towards a Polanyian Perspective on Fair Trade: Market-based Relationships and the Act of Ethical Consumption - Watson, Matthew (Global Society: Journal of Interdisciplinary International Relations, 2006)
Fair trade requires that developed country consumers engage in market-based transactions with developing country producers. Yet this is not market trade in any straightforward sense, because the purchase of fairly traded products brings consumers into two market relationships at the same time. One is the market relationship through which consumers buy the product itself, which enables them to act altruistically by consciously paying the price premium that the producer receives. The other is the market relationship through which consumers buy the socially reputable knowledge of having helped a distant stranger, which enables them to harness their ostensibly ethical consumption to a knowingly self-interested action. This latter relationship adds a new dimension to orthodox commodity fetishism. A Polanyian perspective is developed to investigate the way in which fair trade reworks the commodity fetish. This serves as a prelude to an extended discussion of the moral status of the behavioural motivations that underpin fair trade consumption.
Political Science; International Relations
Keywords: commodity fetishism; comparative studies; economic consumption & ethics; globalization; international trade; relationship marketing; unfair competition

Beyond Globalization: Capitalism, Territoriality and the International Relations of Modernity - Lacher, Hannes (Routledge, 2006)
Hannes Lacher presents a new critical social theory of international relations that integrates sociology, history and political geography to understand the formation and development of modern international relations. Far from implying a return to state-centrist Realism, this essential new volume leads us towards a critical social theory of international relations that questions the prevailing conceptions of the modern international political economy as a collection of nationally bounded spaces more fundamentally than ever before. It also shows us that capitalist modernity itself was, from the beginning, characterized by the dualism of global economic integration and the fragmentation of political space, which actually stems from the divergent origins of capitalism and territorial sovereignty. This book will be of great interest to al students of historical sociology, political geography, international relations and political science.
Political Science
Keywords: international political economy; international relations

On markets and morality: Revisiting Fred Hirsch - Carvalho, Luís Francisco; Rodrigues, João (Review of Social Economy, 2006)
This article argues for the continuing relevance of Fred Hirsch's The Social Limits to Growth (1976), valued as a critical analysis of the consequences of markets on the moral fabric of society. Two concepts that are fundamental to Hirsch—the commercialization bias and the depleting moral legacy—will be scrutinised. We further claim that this book, by emphasizing the tendency to market expansion and the corresponding commodification of increasing spheres of social life, while simultaneously acknowledging its adverse consequences on the motivational appeal of social and moral norms, offers insights that justify revisiting it.
Economics
Keywords: HIRSCH; Fred; double movement; markets; morality; neoliberalism; second great transformation; social economy

Globalization and contestation: A Polanyian problematic - Munck, Ronaldo (Globalizations, 2006)
The Polanyian problematic presents us with a unified, complex, and dialectical means to interpret globalization and its social contestation by diverse social and political forces. For Karl Polanyi (1886–1964), globalization as we know it would probably be conceived of as an extension of the ‘one big self-regulating market’ he discerned in his day, while his belief that ‘simultaneously a counter-movement was afoot’ provides an interpretative lens to examine the various facets of the counter-globalization movement. The Polanyian problematic of modern history as a ‘double movement’, whereby market expansion and social protection respectively lead phases, provides a useful antidote to all forms of economic reductionism when dealing with globalization on the one hand and political voluntarism with regard to contestation on the other. Basically, globalization is a human construct, and it can thus be deconstructed by society.
Sociology; Political Science
Keywords: Polanyi problem; countermovement; globalization

Economia di mercato e legame sociale: verso nuovi equilibri? - Scidà, Giuseppe (Market economy and social link: towards a new equilibrium?, 2006)
In its first part (§ 2-4), the essay presents an outline of market economy in a globalization era, highlighting its marked changes and the wide fields of its questionable nature. In the second part, some discontinuity features came out in the last decades are shown (§ 5). They are particularly referred to critical analysis and alternative experiences springing up from below, (i.e. associations, groups, movements of the civil society) and meeting in a common attempt of getting economy and people's life with all their social link close again. Afterwards (§ 6- 7), it's stressed as similar concerns can also be found in the very theories by the founder of economic discipline, Adam Smith, and somehow in the works expressing some of the most alternative positions as Karl Polanyi's. Finally (§ 8) it's presented the notion of social capital that is the subject of the present issue of Sociologia del Lavoro. Though arising a lively critical debate, potentially the notion seems to open some new scenarios in the social science in pursuit of a new equilibrium between market economy and social link.
Sociology
Keywords: POLANYI; Karl; 1886-1964; SMITH; Adam; 1723-1790; civil society; globalization; international markets; international relations; interpersonal relations; market economy; social integration; social sciences

The Dialectics of Design - Jenkins, Barbara (Space & Culture, 2006)
The popularity of deconstructivist architecture around the world has invited controversy over the sensationalist design of these buildings. New urbanists, in particular, have criticized decon architecture as alienating and disorienting. From a historical perspective, this opposition between deconstructivists and new urbanists is the latest in a long line of debates over what constitutes "good design." Using a political-economy approach based on the work of Karl Polanyi, this article examines a centuries-long dialectic in design ideology between those who seek to embed design in social mores and those who attempt to "disembed" it from oppressive discourses. This analysis shows that the dialectic of design movements is intintately connected to the development of capitalist markets.
Architecture; Political Science
Keywords: capitalism; cities & towns; cultural studies; deconstructivism; deconstructivism (architecture); dialectic; disembeddedness; embeddedness; good design; modern architecture - 20th century; new urbanism; political economy

Between Aristotle and the Welfare State: The Establishment, Enforcement, and Transformation of the Moral Economy in Karl Polanyi's The Great Transformation - Akturk, Sener (Theoria: A Journal of Social & Political Theory, 2006)
The article examines the transformation of the moral economy in the book "The Great Transformation," by Karl Polyani. Polyani's work has been criticized for having an anti-democratic, Aristotelian, and aristocratic undertones. However, the author claimed that it has been misinterpreted and a communitarian-liberal debate has been brought to clarify the nature of moral economy.
Political Science
Keywords: Great Transformation; The (Book); criticism; democracy; economic policy

The Role of Consensus and Social Homogeneity in the Process of Building Capitalism in Post-communist Countries - Bieliński, Jacek (KONSENS I JEDNORODNOŚĆ SPOŁECZNA W PROCESIE BUDOWANIA KAPITALIZMU W KRAJACH POSTKOMUNISTYCZNYCH., 2006)
The focus of this article is on interpretation of progress of post-communist transformations. Classical approaches, particularly those of Max Weber and Karl Polanyi, rather than modern ones are used as basis for the empirical analysis. I argue that the success of capitalist project, both now and in the past, stems from the ability to work out a general consensus about the preceding economic order. I also claim that ethnic homogeneity can be a favorable factor for the post-communist transformation, especially in its initial phase. Moreover, unlike in fully developed market systems which are more stable and socially diverse, the success of market reforms in post-communist countries negatively correlates with their diversification. One of the main goals of this analysis is to describe empirically what this consensus refers to. Survey research shows that market reforms in former socialist block run more smoothly if the level of social consensus about key values, not necessarily liberal, is high. I analyzed values and attitudes defining the consensus and also the degree of their popularity among economic elites and non-elites. Data used in the analysis comes from the first edition of European Social Survey. (English)
Sociology
Keywords: WEBER; Max; 1864-1920; capitalism; economic sociology; elite; jednorodność; konsens społeczny; markets; post-communism; post-communist transformations; postcommunism; postcommunist societies; social consensus; social homogeneity; socjologia ekonomiczna; społeczna; transformacja postkomunistyczna

The Relationship between Economics and Sociology: The Contribution of Economic Sociology, Setting out from the Problem of Embeddedness - Rizza, Roberto (International Review of Sociology, 2006)
s essay aims to analyse the most recent acquisitions in economic sociology, setting out from the problem of embeddedness. Firstly, the contribution offered by Mark Granovetter shall be illustrated, demonstrating how the interpretation proposed by this scholar is concentrated on a structural-relational perspective that tends to trace the explanation of economic phenomena to a theory of social networks. In order to enrich and integrate this approach, the contribution offered by the new-institutionalist perspective in contemporary economic sociology will be emphasised, which has focused on the social construction of economic institutions. This current has underlined, on the one hand, the cognitive dimension of embeddedness, related to the way in which the uniformities structured by mental processes limit economic reasoning, and, on the other, the cultural dimension of embeddedness, concerning the role of collectively shared representations in the formation of economic goals. It will be concluded by illustrating the acquisitions of some theoretical perspectives linked to the polanyian tradition that have developed a 'plural' conception of economy, founded on the emphasis of socio-regulative principles, such as those of exchange, redistribution and reciprocity, which, in becoming hybrid, give shape to variable and historically anchored economic worlds. The concept of embeddedness roots historically and transmits a vision of economic processes as inseparable from noneconomic institutions
Sociology
Keywords: GRANOVETTER; Mark; economic research; economic sociology; embeddedness; industrial management; social sciences; socioeconomic factors; socioeconomics

Keynes and Polanyi: the 1920s and the 1990s - Polanyi Levitt, Kari (Review of International Political Economy, 2006)
Political Science
Keywords: KEYNES; John Maynard; 1883-1946; international political economy

Karl Polanyi on the Limitations of Formalism in Economics - Stanfield, James Ronald; Carroll, Michael C.; Wrenn, Mary V. (Choice in Economic Contexts, 2006)
This chapter examines Karl Polanyi's critique of formalism in economics and his case for a more institutional economics based upon a reconstitution of the facts of economic life on as wide an historical basis as possible. The argument below reviews Polanyi's argument with regard to the relation between economic anthropology and comparative economics, the contrast between the formalist and substantive approaches to economic analysis, the notion of an economistic fallacy, the most important limitations of the conventional formalist economics approach, and the nature and import of the new departure that Polanyi envisioned. James Ronald Stanfield, Michael C. Carroll, Mary V. Wrenn (2006), Karl Polanyi on the Limitations of Formalism in Economics, in Donald C. Wood (ed.) Choice in Economic Contexts (Research in Economic Anthropology, Volume 25) Emerald Group Publishing Limited, pp.241 - 266
Economics; Anthropology
Keywords: economic anthropology; formalism

L'utopie de l'économie de la connaissance - Azam, Geneviève (Problèmes économiques n. 2901, 2006)
"L'expression "économie de la connaissance" a, en ce début du XXIe siècle définitivement remplacé celle, très en vogue à la fin des années 1990, de "nouvelle économie". Les sociétés les plus avancées auraient désormais atteint un nouveau stade du développement économique dont la connaissance serait le facteur essentiel. Cette idée laisse supposer que jusque-là, celle-ci ne jouait qu'un rôle secondaire dans le processus productif. L'auteur se propose d'expliquer le sens et les implications que ce nouveau statut confère au savoir et à la recherche. Pour mieux comprendre ce qui est à l'oeuvre avec l'invention d'une "économie de la connaissance", elle analyse tout d'abord, à travers l'évolution récente des droits de propriété intellectuelle, les conditions de la transformation de la connaissance en bien économique. S'appuyant sur les travaux de Karl Polanyi, à propos des "quasi-marchandises", l'auteur montre ensuite qu'en réalité celle-ci est une marchandise "fictive" et que la tentative actuelle de lui assigner un rôle instrumental constitue pour elle-même une grave menace." ENG: Building on the work of theKarl Polanyi , on the subject of "quasi-merchandise", the author then shows that, in reality, the latter is a "fictitious" commodity and that the current attempt to assign to it an instrumental role constitutes for itself a serious threat
Economics
Keywords: Lisbon Strategy; biodiversity; economic property; economy of knowledge; ethics; evaluation; intangible assets; intellectual property; patents

Karl Polanyi et les monnaies modernes : un réexamen - Blanc, Jérôme (Contributions à une sociologie des conduites économiques, 2006)
Karl Polanyi a établi une célèbre distinction entre "all purpose money", caractéristiques des sociétés modernes, et "special purpose money", caractéristiques des sociétés anciennes. C'est la conception polanyienne des monnaies modernes qui est critiquée dans ce texte : non seulement elle conduit à considérer que les sociétés modernes ne connaissent pas de "special purpose money", mais en plus elle ne permet pas de renouveler la conception courante de la monnaie (sous-entendu moderne) qui en fait un moyen de paiement universel. ENG translation: Karl Polanyi has established a famous distinction between "all purpose money" characteristic of modern societies, and "special purpose money", characteristic of ancient societies. It is the Polish conception of modern currencies that is criticized in this text: not only does it lead to the view that modern societies do not know a "special purpose money", but also does not allow to renew the current conception of Currency (modern underlining) which makes it a universal means of payment.
Sociology
Keywords: Monnaie moderne. Pratiques monétaires. Polanyi. Monnaies parallèles. Fongibilité. Cloisonnements.; boundaries; fungibility; modern money; monetary uses; parallel currencies

What's Left in the City? What's Right in the Hinterland?: Urban Political Economy in Contemporary Latin America - Goldfrank, Benjamin; Schrank, Andrew (Conference Papers – American Political Science Association, 2006)
This paper accounts for the initial divergence and subsequent convergence of two types of urban political economy-neoliberal and socialist-in late twentieth and early twenty first century Latin America. Part 1 identifies the ideological differences between the two types of city as well as their implications for public policy. While neoliberal cities prioritize accumulation, and therefore use tax breaks, regulatory rollbacks, and the repression of organized labor to attract and retain foreign direct investment, their socialist rivals prioritize distribution, and therefore use social funds,microcredit arrangements, and participatory institutions to employ and empower their citizens. Part 2 treats the emergence of municipal neoliberalism as a secondary city or hinterland reaction to the growth of urban primacy or bias in the 1960s and 1970s. While industrial interests in population centers like Mexico City and São Paulo reaped the rewards of import-substituting industrialization, and therefore organized to defend their gains, their agro-commercial rivals paid a high price for tariffs and foreign exchange controls, and therefore deployed free trade zones (and similar incentives) in places like Chihuahua and Salvador to offset or compensate for the growth of urban primacy. Part 3 traces the origins of municipal socialism to the breakdown of ISI and the accompanying debt crisis in the late twentieth century. While neoliberal municipalities had already embraced the world market, and therefore welcomed structural adjustment at the national level, their socialist rivals feared globalization, and responded with a variety of compensatory measures of their own designed to increase the "social wage" not only in Mexico City and São Paulo but in other major cities like Caracas, Montevideo, and Lima. And, finally, Part 4 concludes by offering a Polanyian interpretation of the seemingly odd convergence of neoliberal and socialist municipalities today-suggesting that, whatever their ideological preferences, municipal authorities must balance accumulation with distribution if they are to survive and prosper in a globalized world. ..PAT.-Unpublished Manuscript
Political Science
Keywords: EPZ; Latin America; Latin America - politics & government; cities & towns; foreign investments; local politics; neoliberalism; participatory budgeting; political planning; socialism

The state we are in: insights from autopoiesis and complexity theory - Gregory, Amanda (Management Decision, 2006)
Purpose - Following Polanyi, this paper aims to suggest that the Industrial Revolution marked a break-point between pre-industrial society (characterised by integration) and industrial society (characterised by differentiation). Design/methodology/approach - As a conceptual paper, the focus is on drawing out the implications of Luhmann's application of the theory of autopoiesis to industrial society. This discussion leads to critical reflection on the state we are in and the active role we can each play in bringing about change. Findings - Differentiation, without an overall co-ordination and control function within society, has led to the sub-systems (and organisations) becoming self-serving or pathologically autopoietic. Society has a capacity for self-observation, through such mediums as the mass media. Alarm at the apparent increasing rate of change in both social and ecological systems reported by the mass media appears to be drawing us towards a second break-point. The outcome of this revolution, should it come about, is impossible to predict but descent into a new "dark age" is an option as is the re-integration of economic activity with social, religious and political functions. Luhmann's autopoiesis provides a convincing explanation for how society is structured and observing the implications of this. The role of the mass media as an observing system and in bringing information about change to society's attention is emphasised. Practical implications - The paper seeks to provide an explanation for how society is structured and demonstrate how society appears to be passively observing the implications of this. Proposals for both restructuring and the actions we, as active citizens and organisational members, can take to redress our current state are advanced. Originality/value - The paper brings together ideas from a diverse range of fields (including autopoiesis, complexity theory, and systems) and applies them to a highly significant topic.
Business; Systems Studies
Keywords: autopoiesis; complexity theory; economic history; industrial revolution; mass media; social history; social systems

Vulnerability and violence: the impact of globalisation - Kirby, Peadar (Pluto, 2006)
'Vulnerability' is now a key term in globalisation studies. It is used to describe how globalisation impacts on individual security, local communities and even global flows of trade, finance and investment. Yet there has been little attempt to interrogate the term and what it is trying to express about globalisation.Peadar Kirby examines what is really meant by 'vulnerability' and links it to new forms of violence that have resulted from decreased security and social cohesion. He argues that vulnerability and violence are characteristic features of a new world order dominated by neoliberal globalisation. Illustrating his argument with a wealth of examples taken from all over the world – from the sudden collapse of the middle class in Argentina to increased levels of poverty internationally – he offers a robust theoretical grounding that will be of use to anyone studying vulnerability and violence and their relation to contemporary globalisation.
Political Science
Keywords: globalization; globalization - economic aspects; globalization - social aspects; international security; national security; political freedom & security; violence; violence in society

Editor's Letter - Lomnitz, Claudio (Public Culture, 2006)
This article previews this edition of "Public Culture" and focuses on Karl Polanyi's theories on capitalism. Polanyi believed in trade liberalization and felt that market regulation is the principal obstacle to collective prosperity. He thought that unregulated markets could bring an end to poverty, and would resolve the chronic dislocation, inequality, and vulnerability that have marked capitalism from its inception. Polanyi demonstrated that market liberalization was only achieved through concerted state intervention.
Anthropology
Keywords: capitalism; free trade; intervention (federal government); poverty; public culture (periodical)

Is There an Opportunity to Establish the Social-Capitalism in the Post Socialist Transition? - Losonc, Alpar (Panoeconomicus, 2006)
Recently Claus Offe has put the question that concerns the fate of the European model of social capitalism: can the model of social capitalism survive the European integration in the context of certain contemporary tendencies? Offe has presupposed that the mentioned model is challenged by the processes of globalisation and the integration of the post socialist countries into the European Union. The working hypothesis of the article is that there is an opportunity to provide a coherent answer to this question. The article consists of two parts. In the first part the author starts with the Polanyi's socio-economic theory and emphasises the importance of this approach for the analysing of the tendencies of capitalism in Western Europe and in the post socialist countries. The author argues that with the Polanyi's theory we are able to explicate the forms of the embedded liberalism in Western Europe after 1945 and the orientation of non-embedded neo-liberalism and the functioning of the workfare state after the crisis of the Keynesian welfare state. Despite the tendencies of the globalisation projected by neo-liberalism, the central element of the social capitalism, namely, the welfare state, remains with the dimensions of the continuity. In the next part the author points out that there is an asymmetrical structure between the Western-Europe and non-Western part of Europe concerning the socialisation of capitalism. The neoliberalisation in accordance with the model of the transfer of ideal-type of capitalism is more strongly implemented in the countries of transition. In addition, the mentioned theoretical approach provides opportunities to explain the failures of implementing of neo-liberalism in the post socialist countries. On the basis of the endorsing of the socio-economic aspects we can address the issue pointed out by Offe.
Economics
Keywords: consumer economics; education and training; health; poverty; property rights; provision and effects of welfare programs; social security and public pensions; socialist institutions and their transitions; socialist systems and transitional economies: political economy; welfare; well-being; and poverty: government programs

Commercialisation, inequality and the limits to transition in health care: a Polanyian framework for policy analysis - Mackintosh, Maureen (Journal of International Development, 2006)
The effects of commercialised health care in embedding, exacerbating and legitimating social and economic inequality are at the root of widespread and recurrent resistance to commercialisation in health. In low income developing countries suffering generalised poverty, and notably in Sub-Saharan Africa, liberalisation of largely unregulated clinical provision has created a substantially informalised, fee-for-service primary health sector which is exclusionary, low quality and under stress. This article argues against a policy assumption that health systems constitute a sector that can benefit like other commodities from liberalisation. Health care is better understood as a ‘fictional commodity’ in the Polanyian sense: inappropriate for full commodification, producing intensely perverse effects when provided on competitive markets, and therefore requiring planning and social constraint. If managed effectively, integrated health systems—like redistributive land reform and effective labour protection—can support a broader economic transition that avoids extremes of inequality; conversely if treated simply as a transitional sector, health systems can make exclusion and inequality much worse. Copyright © 2006 John Wiley & Sons, Ltd.
Economics; Political Science
Keywords: Africa; Sub-Saharan; economic structure; equality; health care reform; liberalism; medical care; medical policy

Governing the Market: The "Political" and the "Economic" in the Restructuring of the "Third World" - Makki, Fouad (Conference Papers – International Studies Association, 2006)
My intention in this paper is to rethink the central contentions of "Globalization Theory" with respect to the relationship of the "state" to the "economy." I will do so via a consideration of recent discussions of the formation of the modern states system within the discipline of International Relations, and Karl Polanyi?s suggestive notion of the "double movement" presently enjoying a revival in sociological studies of the conjuncture of the 1990s. The paper concludes with reflections on how these critical reflections might make it possible to gain a betterappreciation of the current neoliberal restructuring of the erstwhile "Third World." PAT.-Conference Proceeding
Political Science; Sociology
Keywords: economic structure; economics; globalization; international markets; international trade

Food Sovereignty vs. the Corporate Food Regime - McMichael, Philip (Conference Papers – International Studies Association, 2006)
In the twenty-first century, the Polanyian trinity of fictitiouscommodities (land, labor and money) cannot be realised through thetwentieth-century double movement. The regulation of money is no longervested in the state per se, but in instrumentalities such as the IMF, whosetask has become a generalized imperative to reproduce (corporate) moneythrough expending labor and land across the world with decreasing regardfor their sustainability. The construction of a 'world agriculture,'deepening the instrumental use, misuse, and abandonment of natural andsocial resources, unfolds within this general imperative. This paper arguesthat the world-wide food sovereignty movement is the most direct symptom ofthis socio-ecological crisis, embodying a diversity of responsescorresponding to the re-spatialization of social and economic relations inthe corporate food regime. As an expression of the corporate food regime,it reveals both the immanent, and the historical, conditions governing thepolitics of capitalist development under the neo-liberal project. ..PAT.-Conference Proceeding
Political Science
Keywords: commercial products; economic policy; international economic assistance; international economic relations; international studies; sovereignty

The Poverty of the Global Order: Limits of the North/South Division - Mohan, Dia; McMichael, Philip (Conference Papers – International Studies Association, 2006)
Development in the global order is represented in economically reductionist, and in impoverished, terms. The latter refers to the global reproduction of material inequality through the progressive appropriation of alternative visions of development. We argue that the legitimacy of the global order, while represented in terms of 'economic progress,' depends on the progressive naturalization of its epistemological foundations. Here, solutions to the crisis of development become methods of social control through which the dominant visions of what count as viable futures are reproduced and regulated. We critique efforts to humanise development (eg, World Bank, Amartya Sen) as evidence of developmentalism's epistemological crisis. Karl Polanyi's distinction between 'formal' and 'substantive' economy allows us to transcend the reductionism of the scarcity paradigm and revalue difference as the foundation of equality. We consider examples of substantive economy, which realise equality through strategic sovereignty and representational power, in collective and individual terms. Among other such initiatives these represent practical and epistemological 'spaces of hope' for critique of the crisis of the market epistemology that infects both development studies and international studies. Present divisions of the world must be understood as the impoverished outcomes of a market epistemology's construction and development of inequality. ..PAT.-Conference Proceeding
Political Science; International Studies
Keywords: economic development; international organization; international relations; reductionism; social control

An institutionalist perspective on the future of the capitalist world-economy - Özçelik, Emre; Özveren, Eyüp (Journal of Economic Issues, 2006)
The term world-economy in our title must have already given a hint to the careful reader of our purpose in writing this paper: We intend to bridge institutional economics with world-systems analysis in order to enhance the global applicability of the former. World-economy is a term used by Fernand Braudel and Immanuel Wallerstein and means a space defined by the existence of a single division of labor (coexistent with multiple States) whereas world economy would indicate the arithmetic summation of national economies each of which ... In this paper, we elaborate Polanyi's concept of embeddedness so as to construct an institutionalist framework to understand the contemporary world-economy. We contend that embeddedness can be deployed to analyze the so-called "global governance model" (GGM) as the most recent liberal recipe.
Economics
Keywords: embeddedness; global governance model; world-economy

Karl Polanyi in Vienna: The Contemporary Significance of The Great Transformation - Polanyi Levitt, Kari; McRobbie, Kenneth (Black Rose Books, 2006)
Karl Polanyi’s belief that the greatest threat to freedom was a poorly administered economy led him to an economics that was more existential and human-centered. Part I of this book develops Polanyi’s thinking for its significance today through a selection of papers on re-reading his major work entitled The Great Transformation. Part II looks at the life and work of Ilona Duczynska (Polanyi’s wife), political activist, writer and translator and important influence over Karl and his work. Kenneth McRobbie, a poet and historian who teaches at the University of British Columbia, is the editor of Humanity, Society and Commitment. Kari Polanyi Levitt, emeritus professor at McGill University, is the editor of The Life and Work of Karl Polanyi.
History; Political Science
Keywords: autobiography; biography; business & economics

The Dark Side of Embeddeness: The Construction of Economic space and Prestige in Italy 1896-1907 - Polillo, Simone (2006)
The creation of a national economic space is the necessary structural condition for the unfolding of the "self-protective" measures of society that Polanyi analyzed for the post-WWI period, and that he saw as more generally arising in response to free market policies. A national economic space is itself the product of specific institutional arrangements, in particular the state agencies that allow the state to centralize the monetary system in its own hands: in the modern period, these have been central banks. By analyzing a longitudinal sample of the minutes of the meetings of the governing body of the Bank of Italy in its crucial transitional period at the turn of the century (1896-1907), this paper attempts to trace the historical process by which the Italian economy came to be understood as a national space. It shows that the creation of an area of economic prestige measured by the technical success of the central bank and the strength of its relationship with the Treasury was a crucial achievement of the liberal state. ..PAT.-Unpublished Manuscript
Sociology
Keywords: Italy; World War I; banking industry; central bank; embeddedness; manuscripts; monetary policy; money; saving and investment; self-protective measures; state

Lavoro e società industriale. Da Adam Smith a Karl Polanyi - Rosa, Michele La; Rizza, Roberto; Zurla, Paolo (FrancoAngeli, 2006)
KM translate: The volume aims to provide a contribution to the knowledge of the ways of birth and consolidation of the sociological discourse on the economy, at work and their transformations connected to the process of industrialization. The goal, mainly educational, is pursued through the analysis of the contributions that Karl Marx, Emile Durkheim, Max Weber, Joseph Schumpeter, Karl Polanyi, Frederick Taylor and Elton Mayo have offered in this regard. The treatment of these authors, whose total or partial belonging to the sociological context is out of the question, was preceded by a brief analysis of others such as Adam Smith, Charles Babbage and Andrew Ure who, although not strictly belonging to this disciplinary area,
Economics; Sociology
Keywords: DURKHEIM; Emile; MARX; Karl; 1818-1883; SMITH; Adam; 1723-1790; business & economics - labor; economic sociology; industrial revolution; industrialization; sociology of work

The Market, Mind and Rationality. From Vienna to Paris and Back - Rotstein, Abraham (Revue européenne des sciences sociales, 2006)
The mention of the great city of Vienna conjures up the many legacies of music, art and philosophy which it nurtured. But as important as any of these is the more prosaic legacy of the Austrian economists ranging from C. Menger to F. von Hayek. And for some, Vienna may conjure up as well, the debate that K. Polanyi had with these economists in the 1920s. However paradoxical it may seem, it was by virtue of this debate, carried on directly and indirectly over a lifetime, that Polanyi was first and foremost an Austrian, or rather an Austrian «in mirror image ». This was true not only by virtue of the years of his life and his work in Vienna, but more so because he was drawn into and remained a protagonist in the debate around the fundamental issues first raised by the Austrian economists. Menger and his followers E. von Bohm-Bawerk, and L. von Mises had established and diligently pursued much of the agenda of the debate. F. von Hayek was the important representative of this school in recent decades. The particular topic launched by von Mises in 1920 was whether a socialist economy was at all viable without the direction provided by market prices. Regulated or administered prices were bound to lead to economic confusion and the misallocation of resources he maintained.
Economics
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; MISES; Ludwig von; history of economic thought; regulation; socialist economy

Retelling the Great Transformation - Steinberg, Marc (2006)
In this paper I partly retell Polanyi's narrative of the industrial revolution found in his Great Transformation. I discuss how new labor laws consolidated in the 19th century created a legal structure of coerced contractual labor, that did not fit the ideals of free market economics. My retelling focuses on how capitalists in some industries relied on legal coercion of their workers as a means of discipline and labor process control. Through this retelling I demonstrate that Polanyi was still beholden to neo-classical economics in his historical account, errantly seeing the rise of a free market in labor with the Poor Law reforms of 1834 when in fact no such freedom existed. Therefore, he could not provide a fully-fledged institutional analysis of economic embeddedness that lies at the core of his theory. To realize a fully-developed institutional analysis I argue that we need to bring class conflict back into the narrative of institutional change through an analysis of legality and its transformation. I partly map out the outlines of a revised institutional analysis that places emphasis on the spatial organization of power, with 'stateness' conceptualized as a variable in which political power (and more especially authority) is scrutinized as historically accreted institutional structures. I also emphasize the historically specific role of the 'local state' in this narrative. ..PAT.-Unpublished Manuscript
Sociology
Keywords: capitalists & financiers; criminal procedure; industrial laws & legislation; industrial relations; institutional embeddedness; labor laws & legislation; labour laws & legislation; law; quality control

Globalization and Declining Welfare State: The Case of Social Insurance in Turkey - Yasar, Yavuz (Conference Papers – International Studies Association, 2006)
The norm has been rapidly moving from the managed markets under the welfare state back to self-regulating market with the rise of contemporary version of globalization. Today?s globalization is characterized by neoliberal economic policies such as privatization, deregulation, and limited government intervention–despite the growth of government–in open economies. In such an environment, social insurance, one of the defining characteristics of the welfare state, has become a great fiscal burden and not surprisingly on the neoliberal agenda of the institutions of global order such as IMF and the World Bank lately. Solutions required by the neoliberal agenda involve privatization and deregulation of social insurance systems especially in developing countries such as Turkey. Despite the fact that the welfare state played a significant role between 1960 and 1980, social insurance has become one of the few safety nets left for many since the beginning of neoliberal policies in Turkey. Now with the increasing pressure from IMF, Turkish government has been actively working on market oriented solutions for financing health insurance, social security and pensions. However, this trend undermining social insurance jeopardizes at least two, if not more, important issues: sovereignty of the state and future of welfare state as an insurance against the unwanted consequences of self-regulating markets. These two issues are investigated and alternative social policy measures are evaluated in the context of Karl Polanyi?s theory of ?double movement.? ..PAT.-Conference Proceeding
Political Science
Keywords: deregulation; economic policy; economics; globalization; privatization; welfare state